2006
DOI: 10.1074/jbc.m606066200
|View full text |Cite
|
Sign up to set email alerts
|

Trim5α Accelerates Degradation of Cytosolic Capsid Associated with Productive HIV-1 Entry

Abstract: The TRIM5␣ (tripartite motif 5␣ protein) has been linked to the cross-species restriction in human immunodeficiency virus type 1 (HIV-1) infection of non-human cells, but the mechanism by which this occurs remains to be fully elucidated. Here we demonstrate that the capsid (CA) protein of HIV-1 is more rapidly degraded in cells expressing monkey TRIM5␣ than in cells expressing human TRIM5␣. Other proteins encoded by Gag and Pol are not subject to TRIM5␣-mediated accelerated degradation. The accelerated CA degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 44 publications
(41 reference statements)
3
36
1
1
Order By: Relevance
“…While the proteasome might not degrade the RNA directly, we imagine that degradation of the virion protein would render the genome sensitive to degradation by cellular nucleases. These observations are inconsistent with an uncoating mechanism for TRIM5␣, which might be expected to increase the release of the genome and RMT (5,22,23). Finally, our use of retroviral vectors which cannot reverse transcribe due to modification of the PBS demonstrates that sensitivity to TRIM5␣ and proteasomal degradation of the mRNA do not depend on the initiation of RT.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…While the proteasome might not degrade the RNA directly, we imagine that degradation of the virion protein would render the genome sensitive to degradation by cellular nucleases. These observations are inconsistent with an uncoating mechanism for TRIM5␣, which might be expected to increase the release of the genome and RMT (5,22,23). Finally, our use of retroviral vectors which cannot reverse transcribe due to modification of the PBS demonstrates that sensitivity to TRIM5␣ and proteasomal degradation of the mRNA do not depend on the initiation of RT.…”
Section: Discussioncontrasting
confidence: 45%
“…Since MG132 increases the efficiency of lentiviral infection in a cell type-dependent manner (27), we examined the influence of MG132 on restricted particles in comparison to its influence on nonrestricted particles. To minimize unspecific toxicity, we used MG132 at a relatively low concentration (0.5 mol/liter), which is at least four times lower than the concentration used in related studies on retroviral restriction (5,29). Both the RT-proficient (iRV) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This work also found that the rhTRIM5a-mediated degradation of capsid was independent of proteasome function, as proteasome inhibitors did not prevent capsid degradation measured in these experiments. 57 These data form a model in which the stripping of capsid protein from the viral nucleoprotein complexes prevents the complex from completing subsequent steps in the infectious pathway.…”
Section: Proteasome Independent Capsid Degradationmentioning
confidence: 99%
“…57 This work separated cytosolic and vesicular fractions from cells infected with HIV-1 and found that cells expressing rhTRIM5a induced the degradation of viral capsid without affecting other components of the viral nucleoprotein complex. This work also found that the rhTRIM5a-mediated degradation of capsid was independent of proteasome function, as proteasome inhibitors did not prevent capsid degradation measured in these experiments.…”
Section: Proteasome Independent Capsid Degradationmentioning
confidence: 99%
“…Trim5α and its derivative TRIMCyp restrict HIV-1 infection at early steps of the viral life cycle in a speciesspecific manner (6,7). Trim5α mediates the degradation of the capsid (CA) protein of HIV-1 through its ubiquitin E3 ligase activity (8). There is also evidence showing that Trim5α induces rapid uncoating of the HIV-1 capsid, resulting in failure to form a functional preintegration complex (6,9).…”
mentioning
confidence: 99%